Fluoride stability in dentifrices stored in schools in a town of northern Brazil - Jéssica Bandeira MATIAS; Cláudia Said AZEVEDO; Hugo Felipe do VALE; Maria Augusta Bessa REBELO; Flávia COHEN-CARNEIRO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to analyze fluoride stability in dentifrices stored during nine months in schools from Careiro da Várzea, State of Amazonas, Brazil. Analysis of total fluoride concentration, total soluble fluoride, and ionic fluoride in the dentifrice samples was performed in four different time periods: at the time of purchase (baseline); after three months, after six months, and after nine months of storage. Fluoride concentration was determined using a specific electrode (Orion 96-09) connected to an ion analyzer (Orion A-720) and calibrated with fluoride standard solutions containing 2.0 to 32.0 ppm F. The results obtained during the measurements were analyzed by analysis of variance (one-way ANOVA), followed by Tukey's test for comparison of the means. After nine months of storage, total soluble fluoride, the active form of fluoride, decreased by 21.9%. As total soluble fluoride was below the minimum required for anticaries efficacy (1,000 ppm F) in the fourth analysis, it may be concluded that anticaries potential decreased with storage time.